2021
DOI: 10.3389/fphar.2021.701240
|View full text |Cite
|
Sign up to set email alerts
|

Glycyrrhetinic Acid Protects α-Naphthylisothiocyanate- Induced Cholestasis Through Regulating Transporters, Inflammation and Apoptosis

Abstract: Glycyrrhetinic acid (GA), the active metabolic product of Glycyrrhizin (GL) that is the main ingredient of licorice, was reported to protect against α-naphthylisothiocyanate (ANIT)- induced cholestasis. However, its protective mechanism remains unclear. In our work, the cholestatic liver injury in mice was caused by ANIT and GA was used for the treatment. We assessed cholestatic liver injury specific indexes, histopathological changes, bile acid transporters, inflammation and apoptosis. The results of liver bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 39 publications
4
10
0
Order By: Relevance
“…We found that treatment with GA and PCN decreased the amounts of hepatic hydrophobic BAs (LCA, DCA, and CDCA) and increased that of hydrophilic BA (UDCA), indicating their potential to reduce hepatocyte inflammatory responses and liver injury. Our data agree with previous results that GA may protect against ANIT-induced cholestatic liver injury by activating FXR and downstream transporters ( Yan et al, 2021 ). Meanwhile, we found that GA exerted little effect on PXR activation, further supporting that FXR is the critical factor contributing to the choleretic effects of GA.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We found that treatment with GA and PCN decreased the amounts of hepatic hydrophobic BAs (LCA, DCA, and CDCA) and increased that of hydrophilic BA (UDCA), indicating their potential to reduce hepatocyte inflammatory responses and liver injury. Our data agree with previous results that GA may protect against ANIT-induced cholestatic liver injury by activating FXR and downstream transporters ( Yan et al, 2021 ). Meanwhile, we found that GA exerted little effect on PXR activation, further supporting that FXR is the critical factor contributing to the choleretic effects of GA.…”
Section: Discussionsupporting
confidence: 93%
“…These findings suggested that the hepatoprotective effects of GA on LCA-induced cholestatic liver injury might be mediated through inhibition of the TLR/NF-κB pathway. Similar findings have been reported by Yan et al (2021) , and our findings further indicate that TLRs may be the intervention target of GA. Nevertheless, our current work is limited in its investigation of the dose-dependent effect of GA in LCA mice, and further research is necessary to establish a clearer relationship between the dose and hepatoprotective effects of GA. Intriguingly, in addition to the induction of drug-metabolizing enzymes through PXR activation, PCN could also interact with NF-κB to downregulate the expression of chemokines, including CCL2 and CXCL2 ( Okamura et al, 2020 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…According to the intake of the Compound Glycyrrhizin Tablets (containing 25 mg GL/per tablet), the suggested daily intake of GL is 225 mg/day for humans, which is approximately 20 mg/kg/day GA for rats. In our experiments, we used 50 mg/kg/day GA and 500 mg/kg/day EX (suggested daily intake of 5–20 g of liquorice root) for 5 consecutive days, which is close to the normal dose and has also been reported in many publications ( Lin et al, 1999 ; Zhang et al, 2019 ; Yan et al, 2021 ).…”
Section: Methodsmentioning
confidence: 70%
“…Consistent with these results, Kim et al (Kim et al, 2017) reported that RIF-induced hepatotoxicity did not significantly increase ALP level, indicating a type of mixed liver injury via cholestasis and hepatocellular injury. In our study, RIF-induced liver injury was evaluated by measuring ALT, AST, bilirubin changes and H&E staining according to relevant studies (Lin et al, 2019;Fan et al, 2019;Yang et al, 2020c;Yan et al, 2021). We did not measure or quantify CK19 + bile duct mass or ALP levels to analyze hepatotoxicity caused by biliary duct dilatation, which is a limitation in the present study.…”
Section: Discussionmentioning
confidence: 99%